PROBLEMATYKA ZAWIERANIA UKŁADÓW ZBIOROWYCH PRACY W ZATRUDNIENIU TYMCZASOWYM - Wilczyński, Robert (Zeszyty Prawnicze, 2016)
Collective Bargaining Agreements for Temporary Employment Summary The article presents the opinions current in the doctrine and jurisprudence concerning collective bargaining agreements in temporary employment. The differences in the construction of temporary and permanent employment relations make the situation in temporary employment worthy of a separate legal analysis. The issues discussed in this article are the potential for collective bargaining in temporary employment, the legal nature of collective agreements involving an employment agency, and the admissibility of differentiation in terms of subjective and objective legal relations regarding the conclusion of collective bargaining agreements.